The effect of instagram's social media dimensions on purchase intention in compass shoe products with brand equity as mediation in Indonesia - Rijalul Arsyad; Erni Masdupi (Marketing Management Studies, 2023)
This study aims to verify the construct validity of the measurement model, confirmatory factor analysis (CFA) surveillance, social interaction, remuneration, information sharing, entertainment, brand equity, and purchase intention on Compass shoes products in Indonesia, to test the similarity of measurements that have been hypothesized by the model on collected data. In this research, the structural equation model (SEM) is used to answer the research questions. Based on the results of observations of 340 respondents, it is known that the hypothesized measurement model follows the data indicated by the significant fit index and loading factor. Surveillance variable loading factor values ​​are as follows (0.80), (0.43), (0.51), (0.43). The surveillance indicator has a value of more than 0.3, which indicates convergent validity is achieved. Each social interaction variable has a loading factor value as follows (0.57), (0.67), (0.38), (0.70), (0.30). The social interaction indicator has a value of more than 0.3, indicating that convergent validity is achieved. In addition, the remuneration and information sharing variables have factor loading values ​​as follows (0.73), (0.45), (0.44), (0.66), (0.68), (0.68). The remuneration and information sharing indicators have a value of more than 0.3, which indicates convergent validity is achieved. Furthermore, the entertainment variable has factor loading values ​​as follows (0.56), (0.65), (0.36), (0.65). The entertainment indicator has a value of more than 0.3, indicating that convergent validity is achieved. The brand equity variable has factor loading values ​​as follows (0.60), (0.47), (0.43), (0.80). The brand equity indicator has a value of more than 0.3, which indicates convergent validity is achieved, and lastly, the purchase intention variable has a factor loading value as follows (0.85), (0.56), (0.50), (0.48), (0.67), (0.50). The purchase intention indicator has a value of more than 0.3, which indicates convergent validity is achieved. This means that all measures can describe the variables that have been studied.